Amyloid toxicity and platelet‐activating factor signaling1. Issue 6 (25th February 2013) - Sirangelo, Ivana; Irace, Gaetano; Balestrieri, Maria Luisa
Abstract Amyloidosis is the accumulation of insoluble proteinaceous aggregates in vivo and is implicated in many neurodegenerative diseases, including Alzheimer's, Huntington's, and Parkinson's diseases. This article briefly reviews the current knowledge of amyloid aggregate toxicity and inflammatory signaling in the nervous system. In particular, we focus our attention on the role of platelet‐activating factor (PAF) as mediator of amyloid cytotoxicity. J. Cell. Physiol. 228: 1143–1148, 2013. © 2012 Wiley Periodicals, Inc.